2019
DOI: 10.1088/1755-1315/383/1/012035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extraction methods on the nutritional characteristics of milkfish (Chanos chanos Forsskal) bone powder

Abstract: Milkfish (Chanos chanos forskal) bone is one of underutilized part of milkfish and considered as a waste from “satay bandeng” home industry in Banten. The aim of this research was to determine the effect of different extraction methods on the nutritional characteristics of milkfish bone powder. Milkfish bone powder was prepared using two different extraction methods (alkaline and acid). Milkfish filleting waste was boiled with water for 30 min, removed the remaining flesh from the frames, the frames were boile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Along with species, processing methods have been shown to influence the composition of fish bone powder [ 28 , 29 ]. Bechtel et al [ 4 ] reported channel catfish frames to contain around 20% lipid and 16% protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with species, processing methods have been shown to influence the composition of fish bone powder [ 28 , 29 ]. Bechtel et al [ 4 ] reported channel catfish frames to contain around 20% lipid and 16% protein.…”
Section: Resultsmentioning
confidence: 99%
“…Bechtel et al [ 4 ] reported channel catfish frames to contain around 20% lipid and 16% protein. As an alkaline boiling media can denature and hydrolyze proteins and saponify fats [ 29 ], its use for fish bone powder production has been commonly employed, often followed by acid treatment to neutralize the bone mixture [ 5 , 10 , 11 ]. Others have tested the ability of ultrasonic irradiation [ 30 ], proteolytic enzymes and high-pressure wash [ 3 ] to remove excess material from frames.…”
Section: Resultsmentioning
confidence: 99%
“…Fishbone of freshwater milkfish (Chanos chanos) originated from local markets in Daerah Istimewa Yogyakarta, Indonesia. This research adopted a fishbone processing method from the previous study [3]. Afterward, shell powder originated from the blood clamp (Anadara granosa) shell.…”
Section: Fishbone and Shell Powder Processingmentioning
confidence: 99%
“…Fishbone and shell is the leftover of fish and oyster consumption. An accumulation of this waste becomes an environmental problem in several places [2,3]. Fishbone and shell may be useful as a feed supplement to enhance chicken performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation